Therapeutic options for women with infertility before IVF - Н. О. Данкович; О. М. Бабенко (Publishing House TRILIST, 2017)
The number of infertile couples in Ukraine reaches 20%. Elevated prolactin level is significant reason of fertility decline. The aim of the study was to study the effectiveness of the Agnus Castus extract in infertil women with functional hyperprolactinemia who are preparing for IVF. This observational noninterventional cohort study included 30 women who applied for infertility treatment. All women were prescribed a drug that contained a standardized extract of Agnus Castus Ze 440, a tablet of which contains 20 mg of active ingredient, 1 tablet once a day for 3 months. In the course of the study there was a significant reduction in the severity of complaints as a part of premenstrual syndrome, according to the patients assessment using a visual analogue scale. So, after a month of treatment, half as much patients had irritability and mood swings, 1.5 times less often had headache, breast pain, attacks of anger, and almost 3 times - bloating. Such positive dynamics persisted with further therapy: breast pain and bloating almost disappeared (scores of 1.33 ± 0.10 points and 1.18 ± 0.05 points, p < 0.05); other complaints were low intensity (scores of 2-3 points). The level of prolactin in examined women was 47.12 ± 5.34 ng/ml before the start of treatment, and after completion of the treatment it decreased more than two times - 19.08 ± 3.47 ng/ml (p < 0.05). The authors concluded that the use of standardized extract of the Agnus Castus Ze 440 (Prefemin) in women with infertility and functional hyperprolactinemia was highly effective and led to normalization of prolactin level in 76.66% of cases and reduction of PMS clinical manifestations in majority of patients. Thus, studied drug can be considered as an effective therapeutic option in patients before IVF in order to reduce the pharmacological burden and improve the results of infertility treatment.